Organizational spirituality: encouraging meaning and interconnectedness in the workplace - Sanders, Joseph E., III, author (Colorado State University. Libraries, 2003)
This study examined the relationships among and between organizational spirituality, organizational leadership, and organizational commitment based on data collected from 209 hospital employees. The data was analyzed using structural equation modeling to develop and present a theoretical model. Several significant relationships were found among the model's latent and measured variables. The results of the analysis support the conclusion that organizational leadership mediates the relationship between organizational spirituality and organizational commitment. This study provides scholars and practitioners with an empirically tested articulation of spirituality in the workplace.
Keywords: social research